The listening life : embracing attentiveness in a world of distraction - McHugh, Adam S., 1976- (Downers Grove, Illinois : IVP Books, an imprint of InterVarsity Press, 2015)
"Be quick to listen, slow to speak."?James 1:19 How would our lives change if we approached every experience with the intention of listening first? In this noisy, distracting world, it is difficult to truly hear. People talk past each other, eager to be heard but somehow deaf to what is being said. Listening is an essential skill for healthy relationships, both with God and with other people. But it is more than that: listening is a way of life. Adam McHugh places listening at the heart of our spirituality, our relationships and our mission in the world. God himself is the God who hears, and we too can learn to hear what God may be saying through creation, through Scripture, through people. By cultivating a posture of listening, we become more attentive and engaged with those around us. Listening shapes us and equips us to be more attuned to people in pain and more able to minister to those in distress. Our lives are qualitatively different--indeed, better--when we become listeners. --From Amazon.
The listening life -- The king who listens -- Listening to God -- Listening to scripture -- Listening to creation -- Listening to others -- Listening to people in pain -- Listening to your life -- The society of reverse listening.
Includes bibliographical references.
Keywords: Listening -- Religious aspects -- Christianity; Attention -- Religious aspects -- Christianity; Distraction (Psychology) -- Religious aspects